2020
DOI: 10.1371/journal.pone.0240082
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting to take antiseizure medications is associated with focal to bilateral tonic-clonic seizures, as revealed by a cross-sectional study

Abstract: Objectives To evaluate the effects of nonadherence to antiseizure medications (ASMs) and clinical characteristics on seizure control, we employed a prospective cohort cross-sectional study using self-reports and medical records of patients with epilepsy (PWEs). Methods Eight hundred and fifty-five PWEs taking ASMs were enrolled from fourteen collaborative outpatient clinics from January 2018 to March 2019. Questions from the Morisky Medication Adherence Scale were used as adherence self-reports. If a PWE's que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Over one-third of patients with epilepsy are non-adherent to the prescribed treatment regimen, and suboptimal adherence is an important cause of persisting seizures [ 47 ], as well as a risk factor for emergency department visits, hospital admissions, injuries, and even mortality [ 48 ], possibly due to SUDEP [ 49 ]. ASMs that need to be taken less frequently have been consistently associated with better adherence [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over one-third of patients with epilepsy are non-adherent to the prescribed treatment regimen, and suboptimal adherence is an important cause of persisting seizures [ 47 ], as well as a risk factor for emergency department visits, hospital admissions, injuries, and even mortality [ 48 ], possibly due to SUDEP [ 49 ]. ASMs that need to be taken less frequently have been consistently associated with better adherence [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adherence was recorded using the MMAS in 16 of the included studies (see also Table 1 ). In half of those studies, the MMAS-4 [ 8 , 18 , 27 , 37 , 39 , 48 , 50 , 51 ] was used, whereas the other half used the MMAS-8 [ 21 , 23 , 29 , 34 , 52 , 53 , 54 , 55 ]. MMAS evaluates forgetfulness and modification of medication due to an improvement in wellbeing, as well as therapy-associated factors in terms of side-effects.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, a higher number of medications was associated with nonadherence in seven studies. Although Buck et al [ 22 ] identified monotherapy as a predictor of nonadherence, the majority of the studies reviewed found that a higher number of medications per day was associated with nonadherence [ 30 , 36 , 48 , 51 , 54 , 57 ]. Other reasons for nonadherence were the overall complexity of drug therapy [ 19 , 27 , 54 , 55 ], longer treatment duration [ 23 , 38 , 50 ], higher serum AED concentration [ 47 ], and concurrent valproate medication [ 40 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of considerations which emerged from the consensus statements are more specifically relevant to first add-on use. In particular, suboptimal adherence to the prescribed treatment regimen is a common occurrence in individuals with epilepsy [19] and an important cause of persisting seizures [20]. Therefore, it was appropriate for the Panel to recommend that in individuals with uncontrolled seizures, the possibility of inadequate adherence to the previously used monotherapy regimen should be excluded prior to adding another medication.…”
Section: Discussionmentioning
confidence: 99%